A Survey on Caching in Named Data Network - Pakle, Ganesh; Bais, Neha; Manthalkar, Ramchandra (International Journal of Computer Sciences and Engineering, 2018)
To replace the present host-driven IP-based Internet architecture, Content-Centric Networking (CCN) is considered as conceivable substitution and is been developing worldwide. In CCN, the content name rather than IP address of host becomes the primary entity. Content is in this manner decoupled from its location. In addition to other things, this allows the cache to be ubiquitously present. One of the famous examples of CCN is Named Data Networking (NDN). To satisfy the incoming request for data, every node in NDN is permitted to have its own local cache. For productive huge scale content dissemination, NDN is been made a decent architecture because of this. This paper focuses on various caching techniques and explains many of them briefly. NS-3 based Named Data Networking simulator named as ndnSIM is used to assess proposed scheme.